ANALYSIS OF ENVIRONMENTAL NOISE LEVELS IN SONDIR,BORING SOIL WORK AT KADIRI UNIVERSITY - Sony Susanto (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
The campus is critical to learning because it provides a comfortable environment. If there is a disturbance in the environment, such as noise, the teaching and learning process will be disrupted. The purpose of this study was to assess if the noise level outside the campus area next to the recreation area adheres to the calculation standards outlined in Minister of State for the Environment Decree No. 48 of 1996, with a +3 dB tolerance (A). Because the research location is close to a road and adjacent to residences, the results at point 1 meet the quality criterion, however the results at point 2 are one decibel lower. When recreational guidelines are followed, the environment's standard regulations are met.